2020
DOI: 10.1002/bies.201900231
|View full text |Cite
|
Sign up to set email alerts
|

Rhes Tunnels: A Radical New Way of Communication in the Brain's Striatum?

Abstract: Ras homolog enriched in the striatum (Rhes) is a striatal enriched protein that promotes the formation of thin membranous tubes resembling tunneling nanotubes (TNT)-"Rhes tunnels"-that connect neighboring cell and transport cargoes: vesicles and proteins between the neuronal cells. Here the literature on TNT-like structures is reviewed, and the implications of Rhes-mediated TNT, the mechanisms of its formation, and its potential in novel cell-to-cell communication in regulating striatal biology and disease are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 155 publications
(124 reference statements)
1
23
0
Order By: Relevance
“…However, the mechanisms that promotes striatal damage remain unclear, as do the mechanisms via which cGAS activation in HD regulates striatal vulnerability. We speculate that in the striatum, Rhes, a GTPase/SUMOE3-like protein, which increases mHTT solubility and promotes cell-to-cell transport of mHTT via tunneling-nanotube–like membrane protrusions, might participate in cGAS activity and propagate inflammatory and autophagy responses via intercellular signaling ( 99 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms that promotes striatal damage remain unclear, as do the mechanisms via which cGAS activation in HD regulates striatal vulnerability. We speculate that in the striatum, Rhes, a GTPase/SUMOE3-like protein, which increases mHTT solubility and promotes cell-to-cell transport of mHTT via tunneling-nanotube–like membrane protrusions, might participate in cGAS activity and propagate inflammatory and autophagy responses via intercellular signaling ( 99 104 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another outcome induced by TNT-dependent communication is the spread of infectious and neurodegenerative substances [ 23 , 27 , 97 ]. The first evidence provided by the group of Davis showed that membrane nanotubes physically connecting T cells acted as a novel route for HIV-1 transmission [ 21 ].…”
Section: Versatile Functions Of Tntsmentioning
confidence: 99%
“…Impaired autophagy is a wellestablished hallmark of neurodegenerative diseases, including tauopathies [2,23,26,32]. Rhes has an established role in autophagy modulation [10,19,25], including its role in forming tunneling nanotube-like protrusions [28]. These protrusions are thought to facilitate the selective transfer of membrane vesicles and organelles, including lysosomes and endosomes, between cells.…”
Section: Discussionmentioning
confidence: 99%